Spatial Clustering for Identification of ChIP-Enriched Regions (SICER) to Map Regions of Histone Methylation Patterns in Embryonic Stem Cells - Xu, Shiliyang (2014)
Chromatin states are the key to embryonic stem cell pluripotency and differentiation. Chromatin immunoprecipitation (ChIP) followed by high-throughput sequencing (ChIP-Seq) is increasingly used to map chromatin states and to functionally annotate the genome. Many ChIP-Seq profiles, especially those of histone methylations, are noisy and diffuse. Here we describe SICER (Zang et al., Bioinformatics 25(15):1952–1958, 2009), an algorithm specifically designed to identify disperse ChIP-enriched regions with high sensitivity and specificity. This algorithm has found a lot of applications in epigenomic studies. In this Chapter, we will demonstrate in detail how to run SICER to delineate ChIP-enriched regions and assess their statistical significance, and to identify regions of differential enrichment when two chromatin states are compared.